The research and progress of ballistocardiogram-based blood pressure monitoring technology - Zi-Qi CUI; Xiao-Man XING (Yixue xinzhi zazhi)
Blood pressure is one of the most important physiological parameters, which is of great significance to the clinical assessment of individual health status and disease risk management. The ballistocardiogram-based approach to blood pressure monitoring has become one of the hottest topics in the field of blood pressure dynamic monitoring because it can recognize distribution measurement with low load, and quickly reflect blood pressure related information. It overcomes the problems of high load and inconvenient operation of traditional invasive and non-invasive methods. It offers the possibility of useful application in both in clinical and home monitoring. This paper reviews the principles, research progress and prospects of blood pressure monitoring technology based on BCG.